2012
DOI: 10.1016/j.geomorph.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Landscape evolution of a bedrock peneplain on the southern Tibetan Plateau revealed by in situ-produced cosmogenic 10Be and 21Ne

Abstract: : Landscape evolution of a bedrock peneplain on the southern Tibetan Plateau revealed by in situ-produced cosmogenic 10Be and 21Ne.-Geomorphology, [153][154][192][193][194][195][196][197][198][199][200][201][202][203][204] AbstractLow-relief bedrock surfaces that occur at high altitude are a common feature of Cenozoic mountain belts and have often been used to infer a significant amount of rock uplift after their generation at low elevation. The timescale over which such surfaces can be preserved at high ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 88 publications
(131 reference statements)
2
31
0
Order By: Relevance
“…0.04 to 0.2 mm yr −1 ). These low denudation rates are of the same order of magnitude as previously published bedrock and detrital denudation rates in other areas of the plateau (Lal et al, 2004;Kong et al, 2007;Hetzel et al, 2011;Strobl et al, 2012;Li et al, 2014;Rades et al, 2015). The slightly higher denudation rates measured for the two northern tributaries, the Lhasa-He (Kyi) (pt.…”
Section: Abrasion Of Landslide Materialssupporting
confidence: 84%
“…0.04 to 0.2 mm yr −1 ). These low denudation rates are of the same order of magnitude as previously published bedrock and detrital denudation rates in other areas of the plateau (Lal et al, 2004;Kong et al, 2007;Hetzel et al, 2011;Strobl et al, 2012;Li et al, 2014;Rades et al, 2015). The slightly higher denudation rates measured for the two northern tributaries, the Lhasa-He (Kyi) (pt.…”
Section: Abrasion Of Landslide Materialssupporting
confidence: 84%
“…Cosmogenic 10 Be studies demonstrated that denudation rates for the relict landscapes on the southern Tibetan Plateau range from 5 to 11 m Ma -1 (Strobl et al, 2012).…”
Section: Weathering Ratesmentioning
confidence: 99%
“…Within the various geomorphic applications of cosmogenic nuclides, there have been a handful of studies examining the evolution of HLAs (Small et al, 1997;Belton et al, 2004;Hancock and Kirwan, 2007;Vanacker et al, 2007;Strobl et al, 2012;Walcek and Hoke, 2012). These previous studies yielded denudation data rather than simple qualitative assessments.…”
Section: Introductionmentioning
confidence: 99%